Chemical properties of biosilica and bio-oil derived from fast pyrolysis of Melosira varians - Piloni, Roxana Verónica (2017)
This study examined bio-oil and solid products generated from the diatom Melosira varians by fast pyrolysis using a fixed-bed reactor with inert gas flow and a vacuum medium. The effect of temperature (300–700 °C) on product yields, the bio-oil composition and the properties of the solid fraction were evaluated. It was found that the most suitable temperature to obtain significant amounts of high-quality bio-oil (29% yield) was 450 °C, at which point fatty acids appeared as main components. Under all operating conditions a solid material, mainly composed of siliceous frustules, was the most abundant product (59–88% yield). These materials were exhaustively characterized by SEM microscopy, Raman and FT-IR spectroscopy, XRD, elemental analysis and BET surface analyses. The structure and morphology of the biosilica were practically unaltered in the studied temperature range. The conductivity properties of the solids derived from diatom and their composites with carbon nanotubes were determined using cyclic voltammetry.